Art therapy’s engagement of brain networks for enduring recovery from addiction - Quinn, Patricia (Frontiers in Psychiatry, 2025)
The field of addiction in its priority to save lives has emphasized harm reduction and medication therapies that have taken precedence over counseling and psychotherapy. The extensive mental health needs, traumatic histories and cognitive challenges of this population call for more availability of all treatments, but also in-depth treatment for the causes of the addiction. The prevalence of trauma is examined with regard to the challenge it presents in treatment for substance use disorder (SUD), and other comorbidities. Two case examples are offered that exemplify how art therapy expedites key information about underlying trauma. Art therapy is proposed as a treatment approach for SUD for its apparent activation of key neural networks that are also impacted by trauma, and its usefulness in engaging those who have cognitive challenges experientially. Quantitative research is cited that suggests art therapy’s activation of the reward system, which may make art therapy useful in treating the stress and inhibition coefficients of addiction that map to neural networks of addiction. The need for additional empirical research is cited that may improve the efficiency and effectiveness of art therapy and mental health treatment.